Polluting potential of post-Fenton products in landfill leachate treatment - M.R. Sabour; A. Amiri (Global Journal of Environmental Science and Management)
Fenton process, as one of the most conventional advanced oxidation processes, is widely used in the treatment of specific wastewaters, especially landfill leachate. In current study, the main target was to evaluate some neglected aspects of Fenton process in operational applications. Thus, three novel responses were introduced. Mass removal efficiency evaluates overall recalcitrant destruction by establishing organics mass balance pre- and post-Fenton treatment. This differentiates it from conventional chemical oxygen demand removal, since mass removal efficiency basically considers the whole mixture and not only the supernatant. The mass content ratio response provides a measure to evaluate the remaining organics in the sludge. Therefore, a borderline mode considering these limitations leads to best feasible field operations. It was found that mass content ratio for effluent reacted conversely to the sludge in response to coagulation. By increasing the coagulant dosage, coagulation improved and the sludge ratio increased in result. For the mass removal efficiency response, it seemed that appropriate balance of the oxidation/coagulation had considerable role through Fe2+ dosage and [H2O2]/[Fe2+] ratio. Finally, by including further conventional parameters such as sludge quantity, the best operational conditions (X1 = 5.7, X2 = 16, X3 = 207 mM) were optimized by response surface methodology to 27.4% and 14.4% for sludge and effluent mass content ratio, respectively, and 58.1% for mass removal efficiency. The results were in good agreement with determination coefficient (R2) of 0.94–0.97, prediction R2 of 0.80–0.93 and coefficient of variation less than 10.